The shoemaker spinefoot Siganus sutor (Valenciennes, 1835) in the marine waters of Iraq: second appearance and the northernmost record in the northern Indian Ocean - Jawad Laith; Abed Jassim; Resen Amjed Kadhum; Al-Yassein Rajaa; Kulw Ali M. (Oceanological and Hydrobiological Studies)
A new record of Siganus sutor from inland artificial marine extension Shatt al-Basrah canal, south of Iraq, is reported. Two specimens were collected during an ichthyologic survey on 2 November 2021. The specimens are 127 and 129 mm in total length. This record from Iraqi waters represents the species’ second and northernmost appearance in the northern Indian Ocean.